Osservazioni sull’analisi dei paralleli nei dialoghi pseudoplatonici - Pietro Bertocchini (Études Platoniciennes)
In the so-called ‘pseudo-Platonic’ dialogues we are often confronted with passages which echo the authentic dialogues. These parallels, usually interpreted as imitations, deserve to be analysed with greater attention. It is not always immediately clear, for example, which dialogue, whether the authentic or the allegedly spurious one, derives from the other, and if indeed it is possible to establish such a direct relationship between the two. Moreover, the parallels under consideration would require a more accurate description of their features. Only in a limited number of cases they concern the level of expression – for the most part they reproduce contents, themes and motifs. The authors of these “thematic borrowings” – as it is suggested to name them – show a certain degree of independence from their Platonic model, and they sometimes seem to draw inspiration from more than one dialogue at the same time.